Tinjauan Yuridis Tindak Pidana Penggelapan Oleh Karyawan Perusahaan - Afrizal Dwi Prastyo; Tri Susilowati; Moh. Rafi’ie (CV. ITTC INDONESIA, 2023)
The company is a job opportunity for someone who needs work so that the unemployment rate in Indonesia decreases, this is done through Human Resource Development (HRD) as the company's representative in conducting tests from administration to psychology to company HR. However, the fact is that when a criminal act occurs regarding a position as an employee, there are elements that are detrimental to the entrepreneur or company which has accepted workers or laborers in the positions and places required, this is based on Chapter XXIV (Book II) Articles 372 to Article 377 of the Code. The Criminal Law is divided into several categories, up to the crime of embezzlement with the aggravation of Article 52 of the Criminal Code, such as the crime of embezzlement committed by employees. The difficulties faced by companies in enforcing the law often involve holding mediation even though the crime must receive punishment according to the behavior experienced so that the applicable written law continues to be enforced. In this background, the thesis writer uses the (Statute Approach) method so that he will get information from various aspects regarding the legal issue that he is trying to find the answer to. This legal approach is carried out by examining all laws and regulations that are related to legal issues related to the problems discussed by the author of this thesis. After discussing the existing problems, it can be concluded that if based on this, crimes committed by employees against victims as a company wherever they are located, the legal area for reporting to the police becomes the company's authority as the legal consequences that arise when the company enters into an agreement. Working together with employees or workers.